First records of water mites (Acari: Hydrachnidia) from Bhutan, with description of two new species - Pesic, Vladimir; Smit, Harry (Zootaxa, 2007)
New records of water mites (Acari: Hydrachnidia) from streams in Bhutan are presented. Two species new to science are described: Sperchon himalayus sp. nov. and Torrenticola bhutana sp. nov. Furthermore, the first records from Bhutan are given for Monatractides tristis (Lundblad), Testudacarus tripeltatus Walter and Sperchon cf. indicus Kumar et al.